2022
DOI: 10.3390/agriculture12020184
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Land Surface Temperature Images from Unmanned Aerial Vehicle and Satellite Observation for Agricultural Areas Using In Situ Data

Abstract: Remotely-sensed data are a source of rich information and are valuable for precision agricultural tasks such as soil quality, plant disease analysis, crop stress assessment, and allowing for better management. It is necessary to validate the accuracy of land surface temperature (LST) that is acquired from an unmanned aerial vehicle (UAV) and satellite-based remote sensing and verify these data by a comparison with in situ LST. Comprehensive studies at the field scale are still needed to understand the suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 33 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…The current ANN model's prediction is compatible with the validation dataset with an MAE of 0.7861, despite the fact that this dataset was not employed in building an ideal ANN. According to the studies of Awais et al [18], an MAE of 0.78 is an acceptable prediction. Thus, it can be concluded that the overall prediction of ANN is appropriate across the range of statistical parameters.…”
Section: Uncertaintymentioning
confidence: 95%
“…The current ANN model's prediction is compatible with the validation dataset with an MAE of 0.7861, despite the fact that this dataset was not employed in building an ideal ANN. According to the studies of Awais et al [18], an MAE of 0.78 is an acceptable prediction. Thus, it can be concluded that the overall prediction of ANN is appropriate across the range of statistical parameters.…”
Section: Uncertaintymentioning
confidence: 95%
“…e training time of CNN models is quite long, but GPUs help us to solve this issue [62]. Remote images captured from satellite images have a huge importance, but there are some issues in the clarity of images when weather conditions are not so clear which affect the feature selection part of ML process and thus performance degrades [63]. e article described below fills this gap by using a specially designed toolbox.…”
Section: Machine Learningmentioning
confidence: 99%
“…For instance, Awais et al employed the DJI M300 RTK UAV equipped with the DJI Zenmuse XT2 TIR camera to capture TIR images. They converted grayscale values directly into LST, validating the retrieved temperatures using contact thermometers [24]. Naughton et al, utilizing the DJI M100 UAV paired with the DJI Zenmuse XTR TIR camera, obtained high-resolution LST in their study area, assessing daily variations and uncertainties in LST [25].…”
Section: Introductionmentioning
confidence: 99%